The Effect of a Combination of Warm Water Foot Baths and Lavender Essential Oil Aromatherapy on Sleep Quality in Adult Hypertension - Fajriyah, Novita; Susanti, Susanti; Kristiani, Rina Budi; Pramiasti, Hana Dodik; Tang, Li Yoong (Adi Husada Nursing Journal, 2024)
Hypertension is one of the deadliest diseases in the world that can attack anyone, both young and old. Hypertension sufferers have poorer sleep quality compared to those with normal blood pressure. This research is a quantitative research using a Quasi-Experimental Design. This research aimed to determine the effect of a combination of warm water foot baths and lavender essential oil aromatherapy on sleep quality in adults with hypertension. Wilcoxon test results (p = 0.004), which means that there is an effect of combination therapy with warm water foot baths and lavender essential oil aromatherapy on the sleep quality of adults with hypertension. The feet have many thermoreceptors and a high density of capillaries. Soaking your feet in warm water can help prepare the body for sleep naturally and quickly trigger peripheral vasodilation. There are two main ways to apply aromatherapy: topically and through inhalation. Lavender essential oil is said to activate the limbic system, especially the hippocampus and amygdala. Combining warm foot baths with aromatherapy would be a rational approach to the management of sleep disorders in adult patients with hypertension.